Metal-enhanced fluorescence of dyes with quadrupole surface plasmon resonance of silver nanoparticles. Issue 13 (11th May 2022) - Lee, Daedu; Song, Junghyun; Song, Gyounghyun; Pang, Yoonsoo
Abstract : Both dipole and quadrupole surface plasmons of homogeneous silver nanosurfaces amplify a chromophore's emission with substantial spectral overlap via plasmon-coupled emission. Abstract : Silver colloidal films (SCFs) composed of homogeneous 60–220 nm silver nanoparticles were synthesized for optimal fluorescence enhancement of chromophores with the dipole and quadrupole surface plasmons. The fluorescence enhancements with the SCFs of three chromophores, 4-(dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl)-4 H -pyran, 4-dimethylamino-4′-nitrobiphenyl, and coumarin 343 whose emission spectra are centered distinctively in the 470–560 nm wavelength range were compared. Fluorescence enhancements and lifetime changes were investigated via time-resolved fluorescence spectroscopy. The spectral overlap between the chromophore's emission and the dipole or quadrupole surface plasmon resonance (SPR) bands determined the fluorescence enhancements with the SCFs. The dipole and quadrupole SPR bands both appeared to provide effective fluorescence enhancements of chromophores. This knowledge allows researchers to develop sensitive fluorescence sensors by combining nanoparticles with optimal dipole or quadrupole SPR bands in order to achieve fluorescence enhancement of a specific chromophore. The emission dynamics measurements with the SCFs were combined with the finite-difference time-domain simulation results for the local electric fields around the silver nanoparticles to enable discussion of metal-enhanced fluorescence mechanisms, including excitation and emission enhancements.